Pengujian Mutu Silase Ikan Tembang yang Ditambahi Bakteri Asam Laktat (Konsentrasi 20%) Tepung Jagung Dengan Atau Tanpa Larutan Urea - Sujanta Permata Roma; Frans U Datta; Annytha I.R Detha (Jurnal Veteriner Nusantara, 2023)
Fish silage is a semi-liquid product of fish preservatives with the addition of lactic acid, to change the fermentation process that converts carbohydrate sources into acids. Silage can be processed using lactic acid bacteria (LAB). The lactic acid bacteria used in this study were sourced from palm sap isolates. Lactic acid bacteria are a type of beneficial non-pathogenic bacteria that are very helpful in the fermentation process of feed and food ingredients. To determine the effect of adding 10% LAB concentration combined with corn flour and urea on the quality of fish silage and to compare the quality of fish silage based on various aspects of sensory evaluation, namely (aroma, texture, color) and the degree of fish silage. The stages of implementing this research include sampling, making fish silage, fermentation and organoleptic testing and testing the degree of storage. Based on the results of the study, it was found that the results of the organoleptic tests carried out showed that the fish silage produced was of good quality which was characterized by an acidic silage aroma, a silage texture that was not lumpy and not too soft, and an increase in the color of brown silage. The results of the study that the addition of 10% LAB combined with ground maize and urea gave a significantly different effect (P<0.05) on the quality of fish silage. Combined use of fish silage will affect the pH of the silage.